ANALISIS DESAIN, STRUKTUR, DAN METODE PELAKSANAAN PEMBUATAN ORNAMEN BERAT MENARA BABUSSALAM MASJID AS-SUADA WARING - Aminullah, Aminullah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2025)
Mosque minarets are usually tall buildings equipped with loudspeakers for the call to prayer. The shapes of existing mosque towers vary. There are classic shapes, variations, rectangular, spiral towers and cylindrical towers. In classical towers, the ground floor is rectangular, rising to the top to become an octagon, then a cylindrical tower topped by a small dome. The Babussalam Tower is located near the Babus Salam door, door number 1 in the Nabawi Mosque in Medina. It was built in 1307 AD. This tower model was chosen by the owner of the tower construction work for the As Suada Mosque, Waringin Hulu Sungai Utara. This research focuses on ornaments that are quite large, massive and heavy. Its complex shape and high location result in the need to guarantee structural strength and long durability. Failure of this section carries a major risk of accident for anyone crushed below. This requires careful planning and implementation methods to ensure the work is of good quality, both in terms of design accuracy and strength. Writing down the methods that have been used and appear to be successful can hopefully be a trail that can be studied for other complex ornamental structures in the future.